The business of corporate learning insights from practice - Ben-Hur, Shlomo, 1962- (Cambridge University Press, 2013)
"Corporate learning functions are now an established part of many of the world's leading multinational firms. In this book, Shlomo Ben-Hur demonstrates how corporate learning can and should have an integral, strategic, role in a company. Based on firsthand experience, Ben-Hur provides a practical guide to setting up or restructuring a corporate learning function within a company, covering its seven key activities. He identifies and elucidates the key decision points in this process. But The Business of Corporate Learning is much more than a 'how-to' guide. For the first time, this book sheds light on the reasons for success or failure in the strategic deployment of corporate learning. Real-world case studies are used to illustrate the potential pitfalls and demonstrate how - when successfully integrated into the company's strategic management system - corporate learning is able to deliver tangible business results"--